Comparative Effectiveness of First Antiretroviral Regimens in Clinical Practice Using a Causal Approach. Issue 39 (September 2015) - Cuzin, Lise; Pugliese, Pascal; Allavena, Clotilde; Katlama, Christine; Cotte, Laurent; Cheret, Antoine; Cabié, André; Rey, David; Chirouze, Catherine; Bani-Sadr, Firouze; Flandre, Philippe
Abstract : Abstract: The objective of this study was to estimate the cumulative incidences of failure by months 12 (M12) and 24 (M24) for the most prescribed first-line anti-retroviral regimens (ART). It is retrospective analysis of a prospectively collected database. All patients who initiated their first ART with the most prescribed regimens between 1st January 2004 and 30th June 2013 in 12 large HIV reference centers in France were included. The outcome was treatment failure—defined by any treatment modification for virological or tolerability reasons—and comparisons between regimens were carried out at M12 and M24. Adjusted and weighted methods via the propensity score (PS) were used to compare the effectiveness of the first antiretroviral regimens. Potential confounders of the treatment-outcome association were used to estimate PS with multinomial logistic regression. Overall, 3128 and 2690 patients were included in the M12 and M24 analyses, respectively. Patients received 5 different regimens (ABC/3TC with ATV/r or DRV/r, TDF/FTC with ATV/r, DRV/r, or EFV). Failure was reported in 25% and 42% at M12 and M24, respectively. Patients who received TDF/FTC/EFV had a significantly higher proportion of failure at M12 by comparison with TDF/FTC with DRV/r (reference), but not at M24. Patients in the 3 other groups had a trend toward a higher proportion of failure at M12 although not statistically significant. No difference was found at M24. Using data from a large prospective cohort, we found that boosted atazanavir and darunavir had comparable effectiveness, whatever the associated NRTIs, whereas efavirenz-based regimens were relatively less performing on the short term.